(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
The studyexplores lecturers’ usage of digital software platforms for re-engineering pedagogical transformation in selected tertiary institutions in Rivers State for sustainable national development. With the growing demand for digital integration in education, the role of software packages such as Zoom, Google Classroom, Microsoft Office and others has become critical in enhancing teaching and learning processes. This study adopted the descriptive survey design. The study was guided by two specific objectives, two research questions and two hypotheses.The population of the study stood at 62,which comprised of 40lecturersdrawn from the Department of Educational Management, Rivers State University and 22 lecturersdrawn from theDepartment of Educational Management, Ignatius Ajuru University of Education. The census sampling technique was deployed while the entire population was used for the study due to its manageable size. Data was collected using a self-structured questionnaire titled “lecturers’ usage of digital software packages for re-engineering pedagogical transformation (LUDSPRPT)” The reliability of the instrument was done using test re-test method. Scores obtained were correlated using Pearson Product-Moment Correlation Coefficient and it yielded a reliability coefficient of 0.77. Research questions were answered using Mean and Standard Deviation, while the t-test statistical tool was used in testing the formulated hypotheses at 0.05 level of significance. The study revealed that while a good number of lecturers areawareof and utilize basic software packages there still remains a gap in the strategic integration of advanced educational tools for reengineering pedagogical transformation within the tertiary educationlandscape. It was further revealed that to a high extent lecturers apply Microsoft PowerPoint for effective instructional delivery in Rivers State University and Ignatius Ajuru University of Educationrespectivelywhileto a moderate extent,lecturers apply Zoom for effective instructional delivery. Based on the findings, the researchers recommended, among others, thattargeted digital literacy trainingshould be encouraged to foster effective and innovative pedagogical practices through technology.